2009
DOI: 10.2500/ajra.2009.23.3345
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Brain Perfusion Single-Photon Emission Computed Tomography and Magnetic Resonance Imaging in Patients with Post-traumatic Anosmia

Abstract: Background Loss of smell is a problem that can occur in up to 30% of patients with head trauma. The olfactory function investigation methods so far in use have mostly relied on subjective responses given by patients. Recently, some studies have used magnetic resonance imaging (MRI) and single-photon emission computed tomography (SPECT) to evaluate patients with post-traumatic anosmia. The present study seeks to detect post-traumatic anosmia and the areas in the brain that are related to olfactory impairment by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 19 publications
1
39
1
Order By: Relevance
“…In contrast to previous studies, this study was only able to confirm a marginally significant association between posttraumatic temporal lesions and olfactory dysfunction when applying the Bonferroni adjustment [14,15,32]. Perhaps this was due to the low number of patients in the left and right temporal lesion groups (n ¼ 11 and 14).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…In contrast to previous studies, this study was only able to confirm a marginally significant association between posttraumatic temporal lesions and olfactory dysfunction when applying the Bonferroni adjustment [14,15,32]. Perhaps this was due to the low number of patients in the left and right temporal lesion groups (n ¼ 11 and 14).…”
Section: Discussioncontrasting
confidence: 84%
“…These effects were strongest in pre-frontal regions and weaker in the temporal lobe [14]. When using SPECT to investigate brain activity in posttraumatic anosmia, researchers found reduced perfusion in frontal, left parietal and left temporal regions [15]. Another study confirmed reduced metabolism in the median prefrontal cortex and the orbitofrontal cortex of patients with posttraumatic anosmia [16].…”
Section: Introductionmentioning
confidence: 93%
“…Other imaging modalities such as single-photon emission computed tomography (SPECT) and positron-emission tomography (PET) have been investigated in patients with olfactory dysfunction with promising findings [62][63][64]. However as they were not used in patients whose loss was specifically posttraumatic loss the diagnostic role of these tests remains to be elucidated.…”
Section: Neuroimagingmentioning
confidence: 98%
“…16 A role for direct brain injury is also supported by many studies showing abnormalities on MRI in frontal lobes as well as olfactory bulbs, and a recent study with single-photon emission CT even demonstrated hypoperfusion of parietal and temporal lobes in patients with posttraumatic anosmia compared with patients with similar trauma but normal sense of smell. 15 Local exposures to toxins such as ammonia, gasoline, hairdressing chemicals, and others can cause permanent smell dysfunction. 18 Adverse reactions to pharmaceuticals can also cause toxic damage to the olfactory function, both systemically 19 (especially with chemotherapy) and local, such as the cases of anosmia found to be caused by the topical application of intranasal preparations containing zinc, which were marketed as a treatment for upper respiratory infections.…”
Section: Common Etiologies/associationsmentioning
confidence: 99%